2022
DOI: 10.1002/jsp2.1218
|View full text |Cite
|
Sign up to set email alerts
|

Species variation in the cartilaginous endplate of the lumbar intervertebral disc

Abstract: Backgrounds Cartilaginous endplate (CEP) plays an essential role in intervertebral disc (IVD) health and disease. The aim was to compare the CEP structure of lumbar IVD and to reveal the detailed pattern of integration between the CEP and bony endplate (BEP) from different species. Methods A total of 34 IVDs (5 human, 5 goat, 8 pig, 8 rabbit, and 8 rat IVDs) were collected, fixed and midsagittally cut; in each IVD, one‐half was used for histological staining to observe the CEP morphology, and the other half wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…The two pain‐related phenotypes have been used as evaluation indicators in cartilage endplate tissue and subchondral bone. 31 , 32 , 33 With tissue damaged, DRG neurons are highly sensitive due to the activation of nociceptors by various neurotransmitters, including SP and CGRP, released by nociceptive nerve fibers, resulting in hyperalgesia. Thus, we detected the ingrowth of SP + and CGRP + sensory never fibers in the subchondral bone of C4/5 FJs and the endplate of IVDs in the same segment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The two pain‐related phenotypes have been used as evaluation indicators in cartilage endplate tissue and subchondral bone. 31 , 32 , 33 With tissue damaged, DRG neurons are highly sensitive due to the activation of nociceptors by various neurotransmitters, including SP and CGRP, released by nociceptive nerve fibers, resulting in hyperalgesia. Thus, we detected the ingrowth of SP + and CGRP + sensory never fibers in the subchondral bone of C4/5 FJs and the endplate of IVDs in the same segment.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that nerve ingrowth and secretion of pain‐related factors are two common phenotypes of cervical degeneration. The two pain‐related phenotypes have been used as evaluation indicators in cartilage endplate tissue and subchondral bone 31–33 . With tissue damaged, DRG neurons are highly sensitive due to the activation of nociceptors by various neurotransmitters, including SP and CGRP, released by nociceptive nerve fibers, resulting in hyperalgesia.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the rat IVD is hallmarked by differences in its dimensions, cell populations (predominantly notochordal cells instead of chondrogenic NP cells), endplate organization, and so forth. 25 , 27 , 57 , 58 , 59 , 60 , 61 Moreover, the model employed involves a more acute disc degeneration model rather than the commonly chronic degenerative processes involved in human discogenic pain. 58 , 62 How these differences might negatively or positively impact the therapeutic potential of a vertebral MSC transplantation strategy remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the translatability of the results in our rat model to a human scenario remains to be confirmed. Specifically, the rat IVD is hallmarked by differences in its dimensions, cell populations (predominantly notochordal cells instead of chondrogenic NP cells), endplate organization, and so forth 25,27,57–61 . Moreover, the model employed involves a more acute disc degeneration model rather than the commonly chronic degenerative processes involved in human discogenic pain 58,62 .…”
Section: Discussionmentioning
confidence: 99%
“…Resist fluid flow in and out of the disc and maintain a uniform stress distribution across the IVD, 86,223,224 and prevent the disc from herniating or bulging 9,223,224 Distribute load during joint movement and provide lubricated (low friction) movement 37 Withstand compressive loads to the IVD and maintain the BEP-CEP interface through fluid pressure 1 Confine the NP laterally, 7 and anchor for the IVD to the VB. 48…”
Section: Primary Mechanical Functionmentioning
confidence: 99%